Hydrotropism: analysis of the root response to a moisture gradient - Antoni, Regina; Dietrich, Daniela; Bennett, Malcolm J.; Rodriguez, Pedro L. (Springer Verlag, 2016)
Hydrotropism is a genuine response of roots to a moisture gradient to avoid drought. An experimental system for the induction of hydrotropic root response in petri dishes was designed by pioneering groups in the field. This system uses split agar plates containing an osmolyte only in a region of the plate in order to generate a water potential gradient. Arabidopsis seedlings are placed on the MS agar plate so that their root tips are near the junction between plain MS medium and the region supplemented with the osmolyte. This elicits a hydrotropic response in Arabidopsis roots that can be measured as the root curvature angle.